DIGITAL TRANSFORMATION AND E-COMMERCE ADOPTION AMONG SMALL BUSINESSES IN DEVELOPING AFRICAN ECONOMIES: EVIDENCE FROM ETHIOPIA AND UGANDA - Moses, Victor (UIN Sunan Gunung Djati Bandung, 2023)
Digital transformation is a crucial driver of economic growth and innovation, particularly in developing economies. This study explores the adoption of e-commerce among small businesses in Ethiopia and Uganda, focusing on the factors influencing digital transformation in these markets. A comprehensive literature review was conducted to synthesize existing research on e-commerce adoption, technological readiness, and the socio-economic challenges faced by small businesses. The findings highlight the pivotal role of technological infrastructure, government policies, and digital literacy in shaping e-commerce adoption. Barriers such as inadequate internet access, limited financial resources, and regulatory hurdles were identified as significant challenges. Conversely, the study found that entrepreneurial orientation and market dynamics foster digital growth and e-commerce participation. This review provides a conceptual framework to understand the complexities of digital transformation in small businesses within developing economies. Recommendations are offered for policy interventions and strategic support to enhance digital integration in these contexts. The study underscores the importance of fostering an enabling environment for e-commerce to thrive among small businesses in Ethiopia and Uganda.